Sutureless and Rapid Deployment Prosthesis in Redo-Bentall Endocarditis - Salvatore Nicolardi; Gabriele De Masi De Luca; Federica Mangia; Cosimo Angelo Greco; Salvatore Zaccaria (Case Reports in Surgery)
Aortic valve replacement (AVR) in a patient with a bio-Bentall conduit can be very challenging, especially if there was a previous endocarditis process for significant morbidity and mortality. We report a case of sutureless AVR in an old patient with a bio-Bentall conduit (Carpentier–Edwards Perimount Magna Ease 25 aortic valve and Hemashield 30 aortic conduit), who developed an endocarditis on aortic prosthesis valve. We believe that sutureless AVR is the best option for redo-operation in older patients with a high surgical risk because it allows for easy rapid deployment implantation, avoids anchoring sutures on a fragile aortic anulus, and reduces cardiopulmonary and aortic cross-clamp times. In this setting, it should be considered as a safe and valid alternative not only to traditional prosthesis but also in selected cases to transcatheter valve-in-valve solutions.